CIRCADIAN OSCILLATORY PATTERNS OF OXYGEN-UPTAKE IN INDIVIDUAL WORKERS OF THE ANT CAMPONOTUS-RUFIPES - Takahashidelbianco, M.; Beneditosilva, A. A.; Hebling, MJA; Marques, N.; Marques, M. D. (Blackwell Science, 1992)
Respiratory rates of individual workers of Camponotus rufipes Fabricius (Hymenoptera: Formicidae) were measured at 25-degrees-C and LD 12:12 h (lights on 06.00 hours), DL 12:12 h (lights on 18.00 hours), LL (850 lux) and DD (red light, 20-30 lux), using the micro-Warburg technique. Worker ants were collected from natural nest during the winter of 1987 in a woodland park in the region of Rio Claro, São Paulo, Brazil. The respiration of ants showed a circadian rhythm with acrophase ranging from 20 h 41 min to 01 h 18 min and from 10 h 32 min to 12 h 22 min at LD and DD, respectively. In constant darkness the rhythmometric variables were similar to those presented by ants kept at LD 12:12 h. Under constant light no circadian rhythm in the respiration rates was found. A reduction in the amplitude was observed, indicating an inhibitory effect of this light regime on the respiration process.
Keywords: CIRCADIAN RHYTHM; PHOTOPERIOD; RESPIRATION; ANT; CAMPONOTUS-RUFIPES